Impact of Government Incentives on the Development of Small and Medium Scale Entreprises in Nigeria - Ibrahim Hassan Bakari; Maryam Saidu Jen (Research Synergy Foundation, 2021)
In creating employment opportunities and enhancing economic development in any given economy, it is not in doubt that small and medium scale enterprises (SME's) make an enormous contribution in those regards.this study aims to examine the impacts of government incentives on SMEs’ development in Yola, Adamawa State, Nigeria. The study specifically applies the structural equation model as the main methodology for this research while adopting confirmatory factor analysis (CFA), for easier comprehension and emphasis. The study applied two manifest variables of human capacity building, financial incentives. From these overall manifest variables, the study applied 12-dimensional variables from which the study’s questionnaires emanate from. The questionnaire developed was administered by way of a questionnaire survey method to ascertain relevant data from the study area and population. The purposive sampling method was used to selected 360 participants of the study. From the study, the following findings were made of the dimensional variables: levels of participation in human capacity building are rated highest, Level 1 followed by Influences of human capacity building on decision making at Level 2, Applications of lessons learnt from the capacity building in business is at Level 3, Advances made in business following novel knowledge from the capacity building is at level 4, Observed enhancement in business following the applications is at level 5, and Frequency of human capacity building by the government is at the lowest level 6. stringent conditions to access the financial incentives is rated highest, Level 1 followed by Limited access to financial incentives at Level 2, Failures due to absence of Incentives is at Level 3, Observed Improvements in businesses as a result of the incentives is at level 4, frequency of the financial incentives by the government is at the second to the lowest, level 5 and finally, level 6 is the adequacy of financial incentives. The recommendations, amongst other things that adequate steps be taken to provide incentives in human capacity building and financial incentives, bring about development for SMEs. The investigation will aid in evaluating the workability and operations of SMEs in Yola, Adamawa State.